Personality factors and self-reported political news consumption predict susceptibility to political fake news. (May 2021) - Calvillo, Dustin P.; Garcia, Ryan J.B.; Bertrand, Kiana; Mayers, Tommi A.
Abstract: The existence of fake news on social media is likely to influence important issues such as elections, attitudes toward public policy, and health care decisions. Studies have shown that individual differences predict participants' ability to discern real and fake news. The present study examined whether personality factors and news consumption predict an individual's political news discernment. Participants ( N  = 353) judged the accuracy of true and false political news headlines, completed a personality inventory, and reported how many hours they obtained political news from various sources in a typical week. Regression analyses revealed that greater levels of agreeableness, conscientiousness, open-mindedness, lower levels of extraversion, and fewer hours of news consumption were related to better news discernment. Participants also showed a bias toward headlines consistent with their self-reported political ideology, and this bias was related to consumption of ideologically biased news sources. These results extend those that have identified individual differences in news discernment, demonstrating that personality factors and news consumption are related to the ability to discern between true and false political news.